1992
DOI: 10.1104/pp.99.4.1362
|View full text |Cite
|
Sign up to set email alerts
|

Association of 70-Kilodalton Heat-Shock Cognate Proteins with Acclimation to Cold

Abstract: Exposure of young spinach seedlings (Spinacia oleracea L. cv Bloomsdale) to 5 C leads to an increase in the synthesis of several 79-kilodalton proteins that are present in leaf tissue grown at 200 C. Protein sequence analyses and immunological cross-reactivity indicate that this group of proteins belongs to the 70-kilodalton heatshock family. Steady-state transcript levels and protein synthesis are increased two-to threefold within 1 day, but immunoblot analyses suggest that the steady-state concentration of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
57
0
2

Year Published

1993
1993
2011
2011

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(60 citation statements)
references
References 35 publications
1
57
0
2
Order By: Relevance
“…Dehydrins (DHN)/late embryogenesis abundant proteins (LEA)/proteins responsive to abscisic acid (RAB) are the well known classes of COR proteins. Some COR proteins, like Arabidopsis KIN1, show structural similarities to antifreeze proteins (Kurkela and Franck, 1990) and others to a HSP70 chaperon family which is known to have roles in protein transport, folding and assembly/disassembly processes (Neven et al, 1992). Although physiological function of these different classes of COR proteins remains largely unknown, some showed a positive correlation with the degree of freezing tolerance which is enhanced by cold acclimation (Monroy et al, 1993;Houde et al, 1995;Jaglo-Ottosen et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Dehydrins (DHN)/late embryogenesis abundant proteins (LEA)/proteins responsive to abscisic acid (RAB) are the well known classes of COR proteins. Some COR proteins, like Arabidopsis KIN1, show structural similarities to antifreeze proteins (Kurkela and Franck, 1990) and others to a HSP70 chaperon family which is known to have roles in protein transport, folding and assembly/disassembly processes (Neven et al, 1992). Although physiological function of these different classes of COR proteins remains largely unknown, some showed a positive correlation with the degree of freezing tolerance which is enhanced by cold acclimation (Monroy et al, 1993;Houde et al, 1995;Jaglo-Ottosen et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…It is postulated that proteins that display these distinctive properties may have roles in cryoprotection (Thomashow, 1993). Other cold-regulated gene products show similarities to antifreeze proteins (Kurkela and Franck, 1990) or to drought-induced late-embryogenesis-abundant proteins (Gilmour et al, 1992;Neven et al, 1993) and responsive to ABA proteins (Vilardell et al, 1990;Lang and Palva, 1992), which suggests a possible role in preventing ice formation and imparting tolerance to dehydration stress, respectively .…”
mentioning
confidence: 99%
“…This hsp70 from sugarcane could be part of the group of proteins responsible for SsNAC23 translocation from the place of synthesis (cytoplasm) to where it functions (nucleus). Curiously, a spinach homologue of the maize hsp70 has increased levels during spinach cold acclimation (Neven et al, 1992). Recently it was demonstrated that this protein, denominated Hsc70, has chaperone activity in plants of spinach exposed to cold stress (Zhang and Guy, 2006).…”
Section: Discussionmentioning
confidence: 99%